Journal of Historical Sociolinguistics (De Gruyter Mouton, 2015)
The Journal of Historical Sociolinguistics is a peer-reviewed forum for research on the social history of language. JHSL features original contributions on aspects of language and society in the past, including the social embedding of language variation and change, issues of language contact and conflict, historical multilingualism, social stratification of writing skills, the development of language norms and the impact of language ideologies.